Psychometric properties of the self-consciousness scale-revised : a Malay translation - Deanna Arissa Mohd Osman Giani; NurFarhana Ardillah Aftar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Self-Consciousness Scale was originally constructed by Fenigstein, Scheier, and Buss to assess individual differences in self-consciousness. To date, the instrument has not been validated for usage in the Malaysian population. For this research, the revised version of the Self-Consciousness Scale was translated into Malay – the national language of Malaysia. Therefore, the study aimed to measure the psychometric properties of the Malay translation of the SCS (M-SCS), specifically among adults in Malaysia. The translated instrument was administered to a sample of 700 adults aged 18 years old and above through random sampling. Participants were recruited via social media and the questionnaires were distributed in Google Form. The questionnaire consists of an informed consent form, demographic questions, the M-SCS, Self-Absorption Scale, a debriefing, and an appreciation note. Data were analysed via internal consistency, concurrent validity as well as convergent validity against the SAS using the SPSS v.27. It was concluded the M-SCS is reliable and valid for the Malaysian adult population, with a total of 20 items yielding scores for three subscales (public self-consciousness, private self-consciousness, social anxiety).